If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m = n + -4 Reorder the terms: 2m = -4 + n Solving 2m = -4 + n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '2'. m = -2 + 0.5n Simplifying m = -2 + 0.5n
| 21=4v-7v | | 9b-22=7b-16 | | -2(1-6r)=-2+4r | | 4v+6=41-3v | | 4s+14=2s+66 | | 3x^2+6x=168 | | p+p+64=180 | | -3(x-1)=-2x-3 | | 2a-21=a | | 12x-11y=23 | | 3/13=u/10 | | 5(2x+5)-1=-2x | | 2b-48+2b-96=180 | | 3u-64=u | | 10y+9=13y+3 | | 3n+4(5n+2)=8+3n | | 16z-21+2z+39=180 | | -3(1-5m)+4=1-2m | | 7=an-1+-15 | | 4c-65=5c-85 | | 4c-65=5c-68 | | -2+3p=6p-4-2p | | 7y+73=4y+94 | | -5+6m=5m-8 | | t=2t-51 | | 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x |